2011
DOI: 10.1007/s11060-011-0699-x
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric infratentorial ependymoma: prognostic significance of anaplastic histology

Abstract: Pediatric infratentorial ependymomas are difficult to cure. Despite the availability of advanced therapeutic modalities for brain tumors, total surgical resection remains the most important prognostic factor. Recently, histological grade emerged as an independent prognostic factor for intracranial ependymoma. We retrospectively reviewed the treatment outcome of 33 pediatric patients with infratentorial ependymoma. Progression-free survival (PFS) and overall survival (OS) rates were calculated and relevant prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 33 publications
4
11
0
2
Order By: Relevance
“…It is also in our study that the totality of tumour resection proved to be an independent factor that influenced progression-free survival and overall survival in a positive way. Similarly, the observation carried out by Phi et al [4] revealed significantly longer PFS in the group of children who underwent total resection of the tumour ( P  = 0.029).The analysis of 182 cases of ependymoma treatment available in medical literature by Cage et al [1] resulted in a similar conclusion. In patients after total tumour resection, the longest period of PFS and OS was noted independently of location of the tumour and its histopathological type.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…It is also in our study that the totality of tumour resection proved to be an independent factor that influenced progression-free survival and overall survival in a positive way. Similarly, the observation carried out by Phi et al [4] revealed significantly longer PFS in the group of children who underwent total resection of the tumour ( P  = 0.029).The analysis of 182 cases of ependymoma treatment available in medical literature by Cage et al [1] resulted in a similar conclusion. In patients after total tumour resection, the longest period of PFS and OS was noted independently of location of the tumour and its histopathological type.…”
Section: Discussionmentioning
confidence: 55%
“…The role of chemotherapy has been another broadly discussed issue with regard to the treatment of ependymoma. Chemotherapy has been suggested to decrease tumour mass, increase resectability and to avoid the necessity of application of radiation therapy in infants [4]. In our study based on the guidelines of the “Standardised and Modified Programme of Diagnostics and Treatment of Tumours of the Central Nervous System in Children,” chemotherapy was applied in nine (47 %) children older than 4 with diagnosed anaplastic ependymoma and reported tumour residue or tumour progression.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Os ependimomas, em geral, são raros em adultos, principalmente na localização intracraniana, porém, é o tipo de tumor intramedular mais frequente (Schwartz and McCormick 2000;Chang, Choe et al 2002;Reni, Brandes et al 2004;Metellus, Barrie et al 2007;Armstrong, Vera-Bolanos et al 2010;Gilbert, Ruda et al 2010). A maioria das casuísticas é da população pediátrica e de tumores intracranianos, embora com poucos pacientes (Shu, Sall et al 2007;Tihan, Zhou et al 2008;Boop and Sgouros 2009;Zacharoulis and Moreno 2009;Phi, Wang et al 2012;Vaidya, Smee et al 2012). …”
Section: Idadeunclassified
“…A localização supratentorial é descrita como fator de pior prognóstico devido à característica mais infiltrativa no parênquima normal, dificultando a ressecção total (McLaughlin, Marcus et al 1998;Korshunov, Golanov et al 2004;Reni, Brandes et al 2004;Metellus, Barrie et al 2007 (Shu, Sall et al 2007;Tihan, Zhou et al 2008;Phi, Wang et al 2012;Vaidya, Smee et al 2012). Em análise estratificada por idade, os fatores prognósticos foram distintos entre a população adulta e pediátrica: a localização supratentorial apresenta pior prognóstico nos adultos, enquanto que, na população pediátrica, a infratentorial foi pior .…”
Section: Localizaçãounclassified